A comparison of the physical and anthropometric qualities explanatory of talent in the elite junior Australian football development pathway. Issue 7 (July 2017) - Woods, Carl T.; Cripps, Ashley; Hopper, Luke; Joyce, Christopher
Abstract: Objectives: To compare the physical and anthropometric qualities explanatory of talent at two developmental levels in junior Australian football (AF). Design: Cross-sectional observational. Methods: From a total of 134 juniors, two developmental levels were categorised; U16 ( n  = 50; 15.6 ± 0.3 y ), U18 ( n  = 84; 17.4 ± 0.5 y ). Within these levels, two groups were a priori defined; talent identified (U16; n  = 25; 15.7 ± 0.2 y ; U18 n  = 42; 17.5 ± 0.4 y ), non-talent identified (U16; n  = 25; 15.6 ± 0.4 y ; U18; n  = 42; 17.3 ± 0.6 y ). Players completed seven physical and anthropometric assessments commonly utilised for talent identification in AF. Binary logistic regression models were built to identify the qualities most explanatory of talent at each level. Results: A combination of standing height, dominant leg dynamic vertical jump height and 20 m sprint time provided the most parsimonious explanation of talent at the U16 level (AICc = 60.05). At the U18 level, it was a combination of body mass and 20 m sprint time that provided the most parsimonious explanation of talent (AICc = 111.27). Conclusions: Despite similarities, there appears to be distinctive differences in physical and anthropometric qualities explanatory of talent at the U16 and U18 level. Coaches may view physical and anthropometric qualities more (or less) favourably at different levels of the AF developmental pathway. Given these results, future work should implement a longitudinal design, as physical and/or anthropometric qualities may deteriorate (or emerge) as junior AF players develop.